Philippine medical thesaurus on persons related to medical practice in Bikol - Solas, Joy O. (School of Library and Information Studies, University of the Philippines Diliman, 2005)
This research entitled "Philippine Medical Thesaurus on Persons Related to Medical Practice in Bikol" is part of "The Multilingual Philippine Medical thesaurus". This particular research attempted to identify which of the Medical Subject Headings (MeSH) terms on category Persons, can be translated to Bikol. It also aimed to know how these translated Bikol terms are pronounced and what term relationships could be generated for these terms. Furthermore, it sought to recommend solutions to the problems of translating medical terms from English to Bikol. In order to achieve the objectives of this study, a new list of translation tools was presented to a linguist, Ma. Khristina Manuelli, a professor and the Department Chair of the Department of Linguistics. The downloaded medical terms from MeSH (2005) were presented to the informants which consisted of first-language speaker of Bikol. After data gathering, in order to resolve problems in translating Mesh terms into Bikol, the researcher adopted several policies and guidelines developed by previous researchers.